Association of Interleukin-17A with Biomarker Levels in Chronic Kidney Disease Patients - Alkharsan, Noor H (Technium BioChemMed, 2025)
Chronic kidney disease (CKD) considers as a progressive condition correlated with systemic inflammation, which pays to complications such as cardiovascular disease and renal dysfunction. However, Interleukin-17A (IL-17A), a pro-inflammatory cytokine, plays a serious role in immune regulation and inflammation. This research examines the association of serum IL-17A and biomarkers (creatinine, Beta 2 Macroglobulin) levels in patients with CKD. A case-control study was conducted involving 60 CKD patients and 30 healthy controls at Imam Al-Hussein Medical-City hospital in Kerbala, Iraq, from August to October 2024. Blood and urine samples were collected from all participants, and IL-17A were tested utilizing an ELISA kit. The results stated significantly higher serum IL-17A levels in patients with CKD (24.56 ± 9.60 pg/mL) compared to controls (5.65 ± 1.84 pg/mL), p = 0.0007. Moreover, levels of creatinine in CKD patients (0.96 ± 0.51 mg/dL) were significantly elevated compared to controls (0.27 ± 0.10 mg/dL), p = 0.0002. These findings stated that elevated IL-17A levels are associated with CKD and may pay to chronic inflammation, exacerbating renal damage. Furthermore, serum creatinine and Beta 2 Macroglobulin remnants a reliable biomarker for assessing kidney function. Increased IL-17A levels in CKD patients could serve as potential biomarkers for disease progression and targets for therapeutic interventions aimed at mitigating inflammation and improving patient outcomes.